Continuum damage evolution in pb-free solder joint under shear fatigue loadings - Shaffiar, Norhashimah; Loh, W.K.; Kamsah, N.; Tamin, M.N. (2010)
Progressive materials damage process in solder joint under cyclic shear deformation is examined in this study. A 3-D finite element model of a single reflowed SAC405 solder specimen is developed for this purpose. Cyclic relative displacement cycles between zero and 1.0 mm at displacement ramp rate of 2.0 mm/sec. is applied in the direction parallel to the solder/pad interface. Strain rate-dependent response of the solder is modeled using unified inelastic strain equations (Anand’s model) with optimized model parameters for SAC405 solder. Damage initiation is characterized by the inelastic hysteresis energy per stabilized cycle, ΔW. Elastic stiffness of the solder is then degraded progressively using prescribed damage evolution rule. Results show that extensive inelastic strain accumulation is confined to small selected edge regions near the solder/pad interface. The calculated slow inelastic strain rates in the range of 0.24 to 0.29 sec-1 resulted in bulk solder fatigue failure. In the predominantly tensile stress region near the solder/pad interface, inelastic shear strain range parallel to and stress range normal to the interface plane has the greatest magnitude. The inelastic hysteresis energy or work per stabilized cycle has demonstrated to be a better parameter over accumulated inelastic strain per cycle for describing low cycle fatigue failure of solder joints.